Digital Marketing Business Strategy to MSME Performance in the Industrial Revolution 4.0 Era - Setyawati, Amelia; Sugangga, Rayyan; Maula, Farij Ibadil; Rahma, Adelia (Universitas Ciputra Surabaya, 2023)
This research examines how digital marketing helps SMEs in the industrial era 4.0. Seeing the phenomenon that is currently growing rapidly in the world of SMEs is very interesting and unique, the strategy for SMEs with technology needs to be studied in depth, hence the need for this research to use a qualitative descriptive method. This research examines the actors in the clothing business (distribution). This survey covers six owners and staff distribution. Observation, documentation, and participant in-depth analysis of data. Based on the results of research that has been interpreted with relevant previous research, that apparel SMEs in the industrial era 4.0 require conventional to digital growth strategies. Tokped, shopee, WhatsApp Business, and Instagram show that merchandise distortion has grown. Distortion works with small or independent bands with fans to create a selling environment. Distortion Merchandise band support pressure, goods and shipments, as well as buying and selling. On the other hand, Awesam is active in marketplaces and social media, from tokped, shopee, Lazada, Instagram, Tik Tok, and WhatsApp Business to the Awesam website which is at the top when it comes to